Barriers, attitudes and perceptions to physical activity among pregnant women in Ibadan, Nigeria and the associated factors: a mixed method study - Favour Suberu; Ikeola A. Adeoye (BMC, 2024)
Abstract Background Physical activity has several health benefits during pregnancy. However, it remains low among pregnant women because of various barriers. This study assessed the attitude, perception, barriers to physical activity during pregnancy and the associated factors. Method We conducted a cross-sectional study using a sequential explanatory mixed method among 465 pregnant women attending antenatal care from four healthcare facilities in Ibadan, Nigeria. Data was collected using a pretested interviewer-administered questionnaire, and we conducted four focus group discussions. Using the Barriers to Physical Activity during Pregnancy Scale questionnaire, we assessed the barriers based on the socioecological theory. The explanatory variables included sociodemographic characteristics, obstetric factors, past obstetric history and physical activity-related issues. Data were analysed using univariate and bivariate methods (independent T-tests and ANOVA), and multiple linear regression was at 5% significance. We applied thematic content analysis to qualitative data. Results The mean age of the participants was 29.22 + 5.01 years. The mean ± SD of the total physical activity barrier score (PABS) was 85.35 ± 22.82. The PABS for the subscales were intrapersonal barriers (34.46 ± 8.79), non-pregnancy intrapersonal barriers (14.47 ± 5.67), and interpersonal barriers (11.67 ± 4.25), environmental, political and organisational barriers (24.766 ± 8.82). The significant relationships between the total score of physical activity barriers and religion (p < 0.030), education (p < 0.000), complaints in pregnancy (p < 0.043), antenatal admission in the hospital (p < 0.004), physical activity advice (p < 0.018), pre-pregnancy physical activity (p < 0.000). Factors associated with physical activity barrier score were maternal education: adjusted β: − 15.26, 95% CI: − 27.83; − 2.69; p = 0.017, antenatal admission adjusted β: 12.20, 95% CI 3.74; 20.67, p = 0.005 pre-pregnancy physical activity: adjusted β: − 12.27, 95% CI − 1.6.5; − 7.99, p = 0.001. Significant themes that emerged in the perception of pregnant women towards physical activity are understanding physical activity, personal experience of physical activity, barriers experienced by pregnant women, the role of support, perceived benefits, and information from health care workers. Conclusion Our study showed that pregnant women attending antenatal clinics in Ibadan, Nigeria, face various barriers to physical activity during pregnancy. Using the socioecological framework, the most commonly reported barriers by our respondents were intrapersonal and environmental barriers. Sociodemographic characteristics, pre-pregnancy physical activity, and antenatal admission were significant factors associated with the total barrier scores of respondents. Healthcare professionals should be trained in promoting physical activity during pregnancy. Tailored interventions are necessary to promote physical activity among pregnant women in Nigeria, including the training of health workers.